(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The fact that many enterprise applications, data, and services are shifting to cloud platforms demonstrates how widespread cloud computing technology has become around the world. Security and privacy are two important concerns with cloud computing. Confidentiality, availability, and integrity are all aspects of the phrase security. Security assurance is a key motivator for cloud adoption and deployment. This study will examine major security and privacy challenges as well as potential solutions in the literature. The classification of cloud computing security issues has been investigated. In addition, it analyses many ineffective solutions found in the literature and makes recommendations for establishing a secure, adaptive cloud environment. Furthermore, Cloud Service Providers (CSPs) can solve the afore mentioned challenges to improve security and privacy.